PESAN KESELAMATAN JALAN DALAM SENI MURAL DI HALTE BUS TRANS KOETARADJA (ANALISIS SEMIOTIKA CHARLES SANDERS PIERCE) - Munawarah, Zikrina (Jurnal Ilmiah Mahasiswa Fakultas Ilmu Sosial & Ilmu Politik, 2021)
Mural is a form of visual communication that implicitly delivers message through the visualization in the painting. However, occasionally the message in mural is incomprehensible for communicant. Thus, an analysis such as this research is needed in order to interpret the message. Each mural is differentiated depending on the theme displayed. One of the themes featured in mural is the message of road safety. The said mural can be seen at three Trans Koetaradja bus stops; the Gunongan, Kerkhof, and Taman Budaya bus stops. These three bus stops are easily recognized by citizens because of its downtown location and are also public facilities. Therefore, the researcher analyzes the mural painted at the bus stop to find out what kind of road safety message depicted therein. This study is carried out in qualitative research approach with semiotic analysis methods proposed by Charles Sanders Pierce, which introduces triadic model, as its framework. The triadic model consists of representment which is the initial form of sign, object which refers to the sign, and interpretant which is the meaning of the sign. This research subsequently puts together a road safety message that is visible from the human, vehicle, road, and environment elements seen in the mural painting. The result of this study indicates that the road safety message can be seen from the mural painting which is the representment, each shape in the image as the object and its meaning is related with one another, which is a road safety message in the form of a persuasion to obey traffic rules. The persuasive message is intended to reduce the number of road accidents and increase public awareness regarding the importance of road safety.